2016
DOI: 10.1039/c6nj00380j
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of supported AuPd nanoalloys mediated by ionic liquid-like functionalized SBA-15: structural correlations concerning its catalytic activity

Abstract: We report highly active catalysts based on mono- or bimetallic Au and Pd nanoparticles supported in ionic liquid-like modified SBA-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…14 However, recent results have demonstrated that bimetallic NPs have unique physico-chemical properties, superior to their monometallic counterparts, owing to the combination of their unique and the induced synergistic effects. 9, [14][15][16][17][18] Yong et al have used density functional theory calculations to investigate the adsorption of CO, HCN and NO on Ag 7 Au 6 clusters for potential application as gas sensors and they found that adsorbates chemisorb on the surface of clusters with exothermic adsorption energies and nite charge transfer. 16 Choi et al decorated SnO 2 nanowire networks with bimetallic PtPd NPs which led to fast response and recovery times during the detection of NO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 However, recent results have demonstrated that bimetallic NPs have unique physico-chemical properties, superior to their monometallic counterparts, owing to the combination of their unique and the induced synergistic effects. 9, [14][15][16][17][18] Yong et al have used density functional theory calculations to investigate the adsorption of CO, HCN and NO on Ag 7 Au 6 clusters for potential application as gas sensors and they found that adsorbates chemisorb on the surface of clusters with exothermic adsorption energies and nite charge transfer. 16 Choi et al decorated SnO 2 nanowire networks with bimetallic PtPd NPs which led to fast response and recovery times during the detection of NO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…19 Fan et al prepared ZnO loaded with PtAu bimetallic NPs, which showed high sensitivity to hydrogen down to the ppm-level, even at room temperature, 20 whereas Hassan et al decorated ZnO nanorods with PtPd bimetallic core-shell NPs for accelerated hydrogen gas detection. 21 Thus, it is crucially important to develop a technological approach which can control alloyed NP properties 15 and to investigate the gas sensing performance of decorated nanocomposites comprising micro-and nanostructured semiconducting oxides and bimetallic NPs. The Ag-based alloys, such as the bimetallic AgPt and AgAu NPs, are of particular interest due to the synergistic effect between the noble metal components, which makes them appealing for surfaceenhanced Raman spectroscopy (SERS) as well as for applications in photocatalysis and sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Damasceno et al reported the preparation of supported AuPd nanoalloys on imidazolium-functionalized SBA-15 and investigated the structural correlations toward 4-nitrophenol hydrogenation reaction. [82] The Au and Pd complex anions were adsorbed due to the anion exchange ability of the functionalized SBA-15 ( Figure 6). Small NPs between 1-5 nm are highly dispersed on SBA-15 and only sparsely observed outside pores.…”
Section: Size-controlled Syntheses Of Metal Nanoparticles On Sba-15mentioning
confidence: 99%
“…Nenhuma redução catalítica foi observada na presença apenas do suporte δ-FeOOH puro, indicando que a atividade catalítica pode ser atribuída exclusivamente as nanopartículas de ouro. 3,20,24,25 Portanto, o uso do δ-FeOOH como suporte para a deposição de nanopartículas de ouro abre novas perspectivas para o emprego destes materiais como precursores para a produção de híbridos multifuncionais baseados em óxidos de ferro (III) decorados com nanopartículas metálicas através do tratamento térmico dos catalisadores AuNPs/FeOOH. 17,26 A cinética da reação pode ser facilmente obtida através dos espectros de absorção UV-vis dependentes do tempo (Figura 6).…”
Section: Redução Catalítica Do 4-nitrofenol Pelos Híbridos Aunps/feoohunclassified